Naturally Occurring Epialleles and Their Roles in Response to Climate Change in Birch - Bowei Chen; Tianxu Zhang; Yile Guo; Lesheng Cao; Xu Zhang; Shahid Ali; Renyi Ma; Linan Xie; Jiang Wang; Gaurav Zinta; Shanwen Sun; Guifeng Liu; et al. (Molecular Ecology, 2025)
Epigenetics has been proposed to be an important mechanism that enables plant species to respond and adapt to environmental and climatic fluctuations and is sometimes entirely uncoupled from genetic variation. Nevertheless, the extent of this uncoupling and the contribution of epigenetics to plant responses to global climate change have not been well studied, particularly in forest trees. Here, we generated a high‐quality genome assembly for Betula platyphylla , a key pioneer species in temperate and boreal forest ecosystems, one of the most sensitive areas to global warming. Extensive multi‐omics sequencing of naturally white birch across the 48 provenances captured their full scope of temperate/boreal forests in Northeast China. Using a genome‐wide association study (GWAS), it was shown that over 55% of differentially methylated regions (DMRs) were spontaneous, independent of genetic factors. More than 30% of the spontaneous DMRs were significantly associated with gene expression, that is, potential epialleles, which are primarily involved in metabolism and responses to abiotic stresses; and 1819 of these epialleles were significantly associated with bio‐climatic variables (i.e., climatic epialleles, cEpialleles). Integrating these cEpialleles into a gradient modelling framework revealed that the natural populations of Asian white birch at high altitude/latitude might be most vulnerable to future climates. Our findings highlight the importance of integrating epigenomic and climatic data sets to forecast the adaptive capacity of a key forest species to rapid climate change.